Public awareness on biodiversity conservation and well-being: case of gunung Gunung Mulu National Park, Sarawak - Ibrahim, Mohamad Syahrul Nizam; Assim, Mohd Ibrani Shahrimin Adam; Johari, Shazali; Wan Mohammad, Syarifah Kamariah; Mohammad Afandi, Syamsul Herman; Hassan, Suziana (Springer, 2022)
Lack of public awareness of biodiversity conservation is the leading cause of biodiversity loss. This needs to be emphasized by stakeholders in the conservation effort, particularly in some major conservation areas, including the UNESCO World Heritage sites of Gunung Mulu National Park (GMNP). As a result of threats such as natural catastrophes, pollution, poaching, and uncontrolled urbanization or human development, GMNP is at risk of being inscribed on the List of World Heritage in Danger. The UNESCO status is possible to be drawn if its criteria are not maintained or degraded due to a lack of emphasis on awareness of the importance of the site. However, it is still limited information on to what extent is the public aware of the importance of biodiversity conservation in GMNP and its relationship to their well-being. Thus, the study aims to examine the level of awareness (knowledge, attitude, and experience) among local community and visitors in GMNP towards biodiversity conservation; and determine their well-being, specifically on environmental, economic, and social factors concerning conservation awareness. A validated questionnaire was distributed to the visitors (n = 87) and local community (n = 99) through an online and face-to-face survey. Based on the awareness constructs, their level of knowledge and experience is high, while attitude portrays a moderate level. The visitors have a higher level of knowledge, attitude, and experience than the local community. The level of education and number of dependents had influenced their awareness of conservation. In terms of well-being, the economic and social factors had significantly predicted awareness accordingly. It shows that the dimensions of the neighborhood, life and social relations, services and facilities, education, culture, and monthly income influence their current level of awareness of biodiversity conservation. The empirical study provides insights into developing a biodiversity conservation framework for GMNP that emphasizes community psychology as part of the social movement toward holistic management in the park.